2015
DOI: 10.3109/03008207.2015.1051224
|View full text |Cite
|
Sign up to set email alerts
|

FGFR3 biology and skeletal disease

Abstract: Fibroblast Growth Factor Receptor 3 (FGFR3) is one of four high-affinity receptors for canonical FGF ligands. It acts in many tissues and plays a special role in skeletal development, especially post-embryonic bone growth, where it inhibits chondrocyte proliferation and differentiation. Gain of function mutations cause the most common forms of dwarfism in humans, and they are also detected in cancer. Triggered by ligand binding or in some cases mutation, FGFR3 activation involves dimerization of receptor monom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…In MC, the expression of Fgfr3 was also increased by the Y367C Fgfr3 mutation. It could be the result of a prolonged half time of the protein because the mutation of the transmembrane domain could delay the turnover and degradation of the activated receptor (54,55). …”
Section: Discussionmentioning
confidence: 99%
“…In MC, the expression of Fgfr3 was also increased by the Y367C Fgfr3 mutation. It could be the result of a prolonged half time of the protein because the mutation of the transmembrane domain could delay the turnover and degradation of the activated receptor (54,55). …”
Section: Discussionmentioning
confidence: 99%
“…The FGF receptor 3 (FGFR3) is a tyrosine kinase receptor, expressed in proliferating chondrocytes and early hypertrophic chondrocytes in the growth plate. Both FGF9 and FGF18 are the major ligands of FGFR3 in the growth plate [ 101 ]. Recently, Shung and coworkers found that FGFR3 expression increases the expression of SOX9 and decreases β-catenin levels in cultured mesenchymal cells [ 102 ].…”
Section: Signaling Pathways In Hypertrophymentioning
confidence: 99%
“…For example, FGFR3 is initially expressed by chondrocytes located in the central core of mesenchymal condensation during early development, then in proliferating and pre-hypertrophic zones of growth plates and articular chondrocytes (6). Mutations in FGFR3 have been linked to a variety of human genetic skeletal dysplasias: gain-of-function mutations in FGFR3 result in chondrodysplasias, including achondroplasia (ACH), hypochondroplasia, and thanatophoric dysplasia (TD), while loss-of-function mutations of FGFR3 lead to camptodactyly, tall stature, scoliosis, and hearing loss syndrome in humans (7,8).…”
Section: Introductionmentioning
confidence: 99%